Cultural intelligence and state suspicion: attachment styles as moderators. (6th February 2017) - Luu, Tuan
Abstract : Purpose: State suspicion is a suspension in employees' cognitive and motivational drives toward the organization. The purpose of this paper is to investigate the role of leaders' cultural intelligence (CQ) in mitigating employees' state suspicion. An understanding was also sought on moderating roles of employees' attachment styles on the negative relationship between CQ and state suspicion. Design/methodology/approach: Harvested from respondents from multinational software companies in Vietnam business context, the data were analyzed through hierarchical multiple regression analysis. Findings: The data provided evidence for the negative effect of leaders' CQ on employees' state suspicion. Employee attachment styles were also found to play the moderating roles for that negative relationship. Originality/value: This research advances suspicion research stream through its convergence with CQ research stream.